Palynological reconstruction of environmental changes in coastal wetlands of the Florida Everglades since the mid-Holocene. Issue 3 (May 2015) - Yao, Qiang; Liu, Kam-biu; Platt, William J.; Rivera-Monroy, Victor H.
Abstract : Palynological, loss-on-ignition, and X-ray fluorescence data from a 5.25 m sediment core from a mangrove forest at the mouth of the Shark River Estuary in the southwestern Everglades National Park, Florida were used to reconstruct changes occurring in coastal wetlands since the mid-Holocene. This multi-proxy record contains the longest paleoecological history to date in the southwestern Everglades. The Shark River Estuary basin was formed ~ 5700 cal yr BP in response to increasing precipitation. Initial wetlands were frequently-burned short-hydroperiod prairies, which transitioned into long-hydroperiod prairies with sloughs in which peat deposits began to accumulate continuously about 5250 cal yr BP. Our data suggest that mangrove communities started to appear after ~ 3800 cal yr BP; declines in the abundance of charcoal suggested gradual replacement of fire-dominated wetlands by mangrove forest over the following 2650 yr. By ~ 1150 cal yr BP, a dense Rhizophora mangle dominated mangrove forest had formed at the mouth of the Shark River. The mangrove-dominated coastal ecosystem here was established at least 2000 yr later than has been previously estimated.